Nectar traits of New Zealand trees vary across climatic zones - van Delden, Johanna M.; Leuzinger, Sebastian; Richardson, Sarah J.; Clearwater, Michael J. (Frontiers in Plant Science, 2025)
IntroductionTo evaluate whether plant traits (nectar volume, concentration, sugar mass, flower fresh mass, and size) vary regionally in response to climate, we examined eight native New Zealand tree species. MethodsFlowers were sampled using micropipettes from seven sites across five climate zones spanning both main islands (37–45°S/170–177°E) after having been bagged for 24 hours. Trait data were standardized (0–1 scale) and pooled into a global dataset for cross-species analysis. We used linear regression to assess correlations between plant traits across and within species, followed by parametric and non-parametric tests to examine regional variation. Generalized additive mixed models (GAMMs) were applied to model trait responses to regional climate factors, identifying significant correlations within and across species. ResultsSampling yielded 4,276 flowers and 2,240 μL of nectar from 164 trees. Nectar volume ranged from 0.3–72 μL, concentration from 0.4–53°Brix, sugar mass from 0.01–13 mg, flower fresh mass from 4–1116 mg, and flower size from 4–54 mm. Across species, nectar concentrations were generally higher in drier regions (Canterbury and Hawke’s Bay) located in the rain shadow of axial mountain ranges on New Zealand’s east coast. Nectar volumes and flower masses were greatest in Dunedin, likely influenced by high relative humidity and low sunshine hours. In Nelson-Tasman and Marlborough, flowers were larger, but this trend was unexplained by climatic factors. Within species, plant traits exhibited regional variation, with highly species-specific trait relationships. GAMMs revealed significant climate-trait correlations in 87.5% of species, with climate variables explaining 18–84% of regional variation. Annual sunshine hours and rainfall had the strongest effects, and South Island nectar contained the highest sugar amounts in 67% of species. DiscussionAlthough no uniform trend was evident across species, nectar volumes tended to be lower in sunnier regions, while flowers were larger and nectar concentrations higher in drier areas. Future studies should examine closely related species with larger sample sizes per region, ideally incorporating microclimate data from standardized measurement periods prior to sampling.